Keterlibatan Islamic work ethics memoderasi pengaruh work overload, role ambiguity, dan stres kerja terhadap turnover intention - Anggy Lia Milfa Sari; Abdul Aziz Nugraha Pratama (Nur Science Institute, 2025)
Employee turnover intention has become a critical issue for organizations because it can disrupt organizational stability and increase recruitment and training costs. This study aims to analyze the effects of work overload, role ambiguity, and job stress on turnover intention, with Islamic work ethics as a moderating variable. This study uses a quantitative approach, with primary data collected via questionnaires distributed to employees of PT Tri Duta Perkasa in Cicalengka, West Java. The data were analyzed using Moderated Regression Analysis (MRA). The results show that work overload and role ambiguity have a positive and significant effect on turnover intention, whereas job stress has a positive but insignificant effect. Furthermore, the interaction effects between Islamic work ethics and the independent variables are not statistically significant, indicating that Islamic work ethics do not moderate the relationship between work overload, role ambiguity, job stress, and turnover intention. In conclusion, work overload and role ambiguity are important factors that determine employees’ intention to leave the organization. In contrast, Islamic work ethics do not function as a moderating variable in this study.